Contemporary trends of witchcraft accusations and resulting violence against children: A scoping review and bibliometric analysis protocol - Cara Spence; Edward Salifu Mahama; Kimberly Jarvis; Mary Zettl; Vida Nyagre Yakong; Mary Ani-Amponsah; Helen Vallianatos; Samuel Adjorlolo; Courage Kosi Setsoafia; Geoffrey Maina; Solina Richter; Pammla Petrucka (PLoS ONE, 2026)
Objective This review seeks to understand the global trends of contemporary witchcraft accusations and related harms against children and adolescents (0–18 years of age). Introduction Witchcraft-related violence against children and adolescents (children) reflects an alarming and understudied phenomenon of socio-culturally legitimated harm around the globe, particularly in sub-Saharan Africa. ‘Witchcraft’ explains the unexplainable, such as strokes of luck and/or misfortune. Witchcraft accusations are linked to illness, sudden death, financial misfortune, miscarriages, financial windfall, disability, birth abnormalities, or rare conditions. Religious entities also levy witchcraft accusations, referring to black magic, evil, works or malicious spirits, to profit off families while harming the accused. These accusations result in marginalization, alienation, slandered reputation, communal expulsion, and violence, causing disfiguration, disability, and death. Children are especially vulnerable to witchcraft-related violence, including human trafficking, and ceremonial and cultural sacrifice. Inclusion criteria This scoping review will examine witchcraft accusations and related harms against children and adolescents (0–18 years of age) globally from 1946 to 2024. Exclusion criteria This scoping review excludes articles that do not report specifics of the accusation, situation, result, age of the accused, or country of origin. Methods This scoping review will follow the Joanna Briggs Institute’s Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) Statement. Articles published from January 1, 1946 to December 31, 2024 will be collected across academic, grey literature and web-based databases. A systematic search strategy will be applied in each database, and all search results recorded. A bibliometric analysis will also be undertaken to systematically and rigorously review the extant literature. Findings of this review will identify areas of collaboration and gaps for further exploration. The literature analysis can raise awareness and inform resource development across health care, education, social work, government, and community sectors to better support victims of witchcraft-related harms.